2021
DOI: 10.4103/jiaphd.jiaphd_75_21
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized Public-Funded Oral Rehabilitation Programs and Oral Health-Related Quality of Life of the Elderly in Rural Kerala

Abstract: Background: Edentulism among the elderly deteriorates the physical, social, and mental dimensions of oral and general health. Objectives: This study compared the changes in oral health-related quality of life (OHRQoL) of the edentulous elderly following prosthetic rehabilitation with complete dentures among beneficiaries of public denture programs. The study also compared the responsiveness of Oral Health Impact Profile-14 (OHIP-14) and Geriatric Oral H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Although the overall findings of this scoping review revealed oral healthcare improvements in various rural communities, the findings also suggested that developing countries face a substantial burden of oral diseases [ 16 18 , 22 24 , 26 , 28 , 29 , 35 , 36 ]. Furthermore, the inclusion of studies evaluating oral health strategies in rural communities of developed countries provided evidence of persistent discrepancies in oral healthcare accessibility and a shortage of oral healthcare professionals, confirming that this burden is of global significance [ 15 , 25 , 27 , 30 34 ].…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Although the overall findings of this scoping review revealed oral healthcare improvements in various rural communities, the findings also suggested that developing countries face a substantial burden of oral diseases [ 16 18 , 22 24 , 26 , 28 , 29 , 35 , 36 ]. Furthermore, the inclusion of studies evaluating oral health strategies in rural communities of developed countries provided evidence of persistent discrepancies in oral healthcare accessibility and a shortage of oral healthcare professionals, confirming that this burden is of global significance [ 15 , 25 , 27 , 30 34 ].…”
Section: Discussionmentioning
confidence: 83%
“…These findings suggest a significant inadequacy and deficiency in the provision of oral health education in developing countries. Similarly, the majority of oral health community engagement programs were implemented in Asia [ 16 , 17 , 23 , 24 , 26 , 28 , 29 , 35 ], where the continent stands out as the only one that has successfully implemented a diverse range of oral health strategies to guide oral health care for various populations, such as children, mothers/caregivers, pregnant women, edentulous individuals, teachers, and geriatric patients. However, the implementation of these strategies may be driven by the objective of mitigating the complex issue of approximately 900 million cases of untreated dental caries, severe periodontal disease, and edentulism prevalent throughout the continent [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations